Assistance in Using Digital Marketing for MSMEs in Banjarmasin City - Jumriani, Jumriani; Mutiani, Mutiani; Ilhami, M. Ridha; Sari, Raihanah; Handy, Muhammad Rezky Noor; Puspita, Rizky Martha Cahya (Universitas Lambung Mangkurat, 2024)
Technological developments continue to develop along with the times. Internet access is part of these developments that have influenced human life. Likewise, in economic activities, internet access contributes to the development of an MSME. Micro, Small and Medium Enterprises (SMEs) utilize information technology to run their business. This article aims to describe digital marketing as a marketing strategy for MSME products in the digital era. This article was compiled from the results of community service carried out on 28 and 29, 2021. The author uses literature studies from various sources and scientific journals in the results analysis section. Service is carried out in two activities. First, a discussion regarding the types of digital-based marketing strategies for Tanggui craftsmen. Second, training on the use of digital access in marketing Tanggui products so that it can increase customer interest. From these two activities, it was identified that participants had a great interest and desire to market their production products through digital marketing to develop and manage their businesses well. Digital marketing can make it easier for MSMEs to provide information, interact directly with consumers and expand marketing access.